Geoambiente e indústria das rochas ornamentais - Martins, O. R. (2010)
The essential aspects of the conflict between the traditional extractive industry, particularly that related to ornamental stones, and the recent priorities of environmental protection required by the contemporary society are described. Within the legal framework of the problem, various criteria for evaluating environmental impacts in the ornamental rock sector are analyzed, as well as the landscape rehabilitations required to quarry owners,thus leading to a conclusion that harmonization of those tendencies with the Portuguese reality is an essential necessity.